Eu queria ver o mar e tô batendo cabeça: (auto)reflexividades sobre a educação superior indígena na/da UEMA - MUNIZ, Sérgio César Corrêa Soares (2023)
This thesis is the result of a theoretical-methodological investment whose motivation is the presence of indigenous people in higher education in Maranhão. The main source of the results presented in this work were the academic experiences of indigenous men and women who attended the first Intercultural Degree for Indigenous Basic Education in the state (LIEBI), offered by the State University of Maranhão (UEMA), between the years 2016 and 2022. In this sense, this work is an attempt to construct an anthropological analysis about the meanings and meanings that indigenous academics and academics of LIEBI have constructed from their formative processes. Academic training has been sought by indigenous people throughout the country as an instrument to strengthen their movements, struggles and demands. Following the trails of ethnography in the interstices, a methodological approach in which the researcher is situated in the "colonial difference" and becomes aware of it, directing his investigations to the social processes and ethical-political projects that he integrates as a participant and active subject, it has been possible to affirm that the crossings made by the indigenous throughout their training in the Indigenous Intercultural Degree of UEMA express the (im)possibilities of interculturality. From the (in)compatibilities between the epistemologies of the self and the epistemology of the academic world, the indigenous people began to weave "gnosiologic arrangements" (COLEHO and MUNIZ, 2020) by appropriating western categories and concepts, by which it has been possible to overcome epistemic collisions – a malaise with academic terms and bureaucracy – and to envision epistemic coalitions, alliances between distinct knowledge matrices, present in the intellectual productions of the indigenous and with which they can fight and resist ethnocentric misconceptions about their lives and their future projects, thus resisting epistemicide and the forces of coloniality.